Experimental and Numerical Simulation of Interlayer Propagation Path of Vertical Fractures in Shale - Xiong, Dong; Ma, Xinfang; Yang, Huanqiang; Liu, Yang; Zhang, Qingqing (Frontiers in Energy Research, 2021)
The complex fracture network formed by volume fracturing of shale gas reservoir is very important to the effect of reservoir reconstruction. The existence of bedding interface will change the propagation path of the hydraulic fracture in the vertical direction and affect the reservoir reconstruction range in the height direction. The three-point bending test is used to test and study the mechanical parameters and fracture propagation path of natural outcrop shale core. On this basis, a two-dimensional numerical model of hydraulic fracture interlayer propagation is established based on the cohesive element. Considering the fluid-solid coupling in the process of hydraulic fracturing, the vertical propagation path of hydraulic fracture under different reservoir properties and construction parameters is simulated. According to the results, the strength of the bedding interface is the weakest, the crack propagation resistance along the bedding interface is the smallest, and the crack propagation path is straight. When the crack does not propagate along the bedding interface, the fracture propagation resistance is large, and the fracture appears as an arc propagation path or deflection. The difference between vertical stress and minimum horizontal stress difference, interlayer stress difference and interface stiffness will have a significant impact on the propagation path of vertical fractures. Large injection rate and high viscosity fluid injection are helpful for vertical fractures to pass through the bedding interface, and low viscosity fracturing fluid is helpful to open the bedding interface. This research work is helpful to better understand the characteristics of bedding shale and the interlayer propagation law of vertical fractures, and to form the stimulation strategy of shale gas reservoir.